Peran Rumah Sakit dalam Pencegahan dan Pengendalian Infeksi di Rumah Sakit - Handriani, Wita; Ginting, Chrismis Novalinda; Nasution, Sri Wahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the role of hospitals in preventing and controlling infections at Royal Prima Indonesia Hospital. The research method uses a cross-sectional study. The study results showed that the chi-square statistical test analysis of the role of hospitals in preventing and controlling infections at Royal Prima Medan Hospital showed a p-value = 0.283, which means the p-value> 0.05. In conclusion, there is no relationship between the hospital's role and the PPI team's compliance in preventing and controlling infections. Suggestions should be made so the hospital can provide ongoing training and education to improve compliance with standard precautions every three months. Keywords: Role of Hospitals, Prevention and Control of Infection